MENINGKATKAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN MEDIA AUDIO VISUAL POKOK BAHASAN MELENGKAPI PUISI ANAK BERDASARKAN GAMBAR MODEL PEMBELAJARAN TEMATIK - Khulasoh, Khulasoh (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research aimed to improve the students, poem writing on topic of completing poems based on the pictures of thematic learning model using audio-visual for the third graders of SD Negeri 1 Rejasari The method used was a classroom action research held in 2 cycles , each cycle had 2 meetings consisting of planning, acting observing and reflecting . The data analysis was by test and non – test techniques, the test was by written test and the non – test was by teacher’s and students’ observation sheet and documentation. Based on the result of the research of the student’s ability in writing poems, the learning completeness in pre cycle was 12,5%, it improved to 42,42% in cycle II and it improved more to 90,37% in cycle III, The teacher ‘s activity in the effort to improve the student’ writing poems in cycle I was 63,04% in cycle and it improved to 93,57% in cycle II. The students’ activity in cycle I was 66,66% in cycle I and it improved to 94,44% in cycle II. Therefore , it could be concluded that thematic learning model by using audiovisual could improve the students’ ability in writing poems in class III SD Negeri I Rejasari.